Correction: Soluble fluorene–benzothiadiazole polymer-grafted graphene for photovoltaic devices. Issue 62 (10th August 2017) - He, Junying; Bao, Feng; Yan, Shuang; Weng, Fangqing; Ma, Rui; Liu, Yanping; Ding, Hao
Abstract : Correction for 'Soluble fluorene–benzothiadiazole polymer-grafted graphene for photovoltaic devices' by Junying He et al., RSC Adv., 2017, 7, 35950–35956.